2014
DOI: 10.1097/meg.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Whipple’s disease concomitant with candida esophagitis and subsequent Giardia lamblia coinfection

Abstract: Whipple's disease is a rare systemic condition resulting from a chronic infection by Tropheryma whipplei. Clinical presentation can be widely heterogeneous, often leading to delayed diagnosis and treatment. Furthermore, little is known about the underlying pathogenic mechanisms, although several abnormalities in immune cell function have been observed. We describe the case of a 51-year-old woman presenting with dysphagia, odynophagia, long-lasting low-grade fever, and malabsorption syndrome who underwent an up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Bacteria that are often co-isolated with Candida spp. from infection sites are staphylococci [10,316], but also less frequent bacteria such as S. marcescens , Tropheryma whipplei or other fungi, for example, C. neoformans [317,318,319].…”
Section: Fungal-bacterial Interactions—niche By Nichementioning
confidence: 99%
“…Bacteria that are often co-isolated with Candida spp. from infection sites are staphylococci [10,316], but also less frequent bacteria such as S. marcescens , Tropheryma whipplei or other fungi, for example, C. neoformans [317,318,319].…”
Section: Fungal-bacterial Interactions—niche By Nichementioning
confidence: 99%
“…Sulis et al [17] have reported a case of TW in which no specific risk factors for opportunistic infections were identified in patients with candidal esophagitis except TW infection; therefore, they hypothesized that the candidal infection was directly related to WD. Moussawi et al [18] have proved using a mouse model that TW alone cannot invade tissues but can smolder in cells, including macrophages, by inhibiting the xenogenic phagocytosis process, a selective autophagy that targets pathogens.…”
Section: Immunoreactivity and Periodic Acid-schiffmentioning
confidence: 99%
“…In some populations, up to 75% of Giardia infections include co-enteropathogens, most commonly with Vibrio cholerae and rotavirus [ 151 ] and elsewhere with norovirus and enteropathogenic E. coli [ 46 ]. Cases of co-infections with Tropheryma whipplei have also been reported [ 152 ]. In rural Ecuador, the OR for diarrhea with rotavirus infection was 6-14.8, but G. lamblia with rotavirus increased the OR to 11-24.13.…”
Section: Determining How Giardia Causes Diseasementioning
confidence: 99%